READING ON ORIENTALIST CLAIMS TOWARDS THE INFLUENCE OF CHRISTIANITY IN THE SUNNAH - Murshid, Abdullah Faiz; Ramli, Nusairah (International Prophetic Conference (SWAN) FPQS USIM, 2022)
Generally, the word ‘Oriental’ is a noun-form that refers to a person or a group of people from the Orient. This word describes anything related to the East, such as oriental landscapes, literature, attitudes, and so on. A person who studies or writes Orient is referred as an “Orientalist”. Specifically, this term refers to the Western theories and theses about Orient. The research aims to refute the claims of orientalists on the influence of Christianity in the Sunnah of the Prophet Muhammad Peace Be Upon Him (PBUH) and to uphold the Sunnah from the claims related to the authenticity of it. In this paper, the researcher starts by identifying the claims of orientalists on the influence of Christianity in the Sunnah. Subsequently, investigate the claim for assurance. Finally, analyze the claims by referring to the Muslims scholars’ views and interpretations.